2008
DOI: 10.1007/s10803-007-0520-z
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Form and Function Level Receptive Prosodic Abilities in Autism

Abstract: Prosody can be conceived as having form (auditory-perceptual characteristics) and function (pragmatic/linguistic meaning). No known studies have examined the relationship between form-and functionlevel prosodic skills in relation to the effects of stimulus length and/or complexity upon such abilities in autism. Research in this area is both insubstantial and inconclusive. Children with autism and controls completed the receptive tasks of the Profiling Elements of Prosodic Systems in Children (PEPS-C) test, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
76
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 38 publications
9
76
1
5
Order By: Relevance
“…Using a complex low-level auditory task, Alcantara also found diminished temporal but intact spectral processing in children with autism (Alcantara et al 2004). Järvinen-Pasley and colleagues (Jarvinen-Pasley et al 2008a) found, using the PEPS-C task (a computerised task that tests both prosody form perception and prosody function perception), that children with autism performed poorer on affective intonation, chunking (phrasing) and long-sound discrimination. Especially the chunking (in which a short silence between words is informative for sentence meaning) and long-sound discrimination (short-sound discrimation was unaffected) suggest that temporal processing was reduced in the autism group as well.…”
Section: Discussionmentioning
confidence: 99%
“…Using a complex low-level auditory task, Alcantara also found diminished temporal but intact spectral processing in children with autism (Alcantara et al 2004). Järvinen-Pasley and colleagues (Jarvinen-Pasley et al 2008a) found, using the PEPS-C task (a computerised task that tests both prosody form perception and prosody function perception), that children with autism performed poorer on affective intonation, chunking (phrasing) and long-sound discrimination. Especially the chunking (in which a short silence between words is informative for sentence meaning) and long-sound discrimination (short-sound discrimation was unaffected) suggest that temporal processing was reduced in the autism group as well.…”
Section: Discussionmentioning
confidence: 99%
“…Also, their ability to perceive pitch in speech may be heightened, but their ability to connect pitch with speech meaning seems to be impaired (e.g. in Järvinen-Pasley, Peppé, et al, 2008, who showed that children were unable to distinguish between interrogative phrases and statements, based on whether the pitch went up or down at the end of the phrase). Thus, the task before a music therapist may be to teach a patient to connect pitch and rhythm cues with meanings.…”
Section: Asd and Auditory Perceptionmentioning
confidence: 99%
“…Specifically, some research groups reported that individuals with ASD exhibited deficits in the comprehension of grammatical cues of word stress (Paul, Augustyn, Klin, & Volkmar, 2005a;Peppé et al, 2007), whereas others have not (Chevallier, Noveck, Happé, & Wilson, 2009;Crossman et al, 2010;Järvinen-Pasley, Peppé, King-Smith, & Heaton, 2008a). A similar pattern of inconsistencies in the results is evident in studies exploring the ability to use stress to perceive phrase structures in individuals with ASD.…”
Section: Introductionmentioning
confidence: 96%